Migration Challenges – Differing Answers? - Raisz, Anikó (Migration and Central Europe: Challenges and Legal Responses, 2024)
This chapter provides an overview of the present book, whose contributions cover different topics related to migration and its role in Eastern Central Europe, while drawing conclusions from the various perspectives provided by the authors. While it is essential to have a holistic view of the legal, political, economic, social, and moral approaches towards migration, it is just as important to see the starting points as well as the real-life experiences when it comes to assessing the situation. Hence, this chapter touches upon various aspects: from roots and terminology issues, through national constitutional, legal, and institutional solutions, to responses given to the phenomenon by the United Nations, the Council of Europe, and the European Union. Keywords: migration, refugee, Eastern Central Europe, national law, EU law, Council of Europe, United Nations